A brief history of The Basarabean Church Magazine (Confluenţe Bibliologice, 2020)
In the article is presented Bessarabian Church magazine, published in 1942 in Balti, Moldova. The content of the magazine is about vary authors, the interesting titles of their articles, but also information about Marshal Ion Antonescu's visit to Bessarabia, especially the one from Balti, on April 11-12, 1942.
Keywords: religious magazines; Bessarabian Church magazine